Interaction of Heparin with Histidine-Rich Glycoprotein and with Antithrombin III - Lijnen, H R; van Hoef, B; Collen, D (Thrombosis and Haemostasis, 1983)
The interaction between heparin, histidine-rich glycoprotein and antithrombin III was studied in purified systems. Histidine- rich glycoprotein binds heparin and thereby interferes with its interaction with antithrombin III, resulting in neutralization of the anticoagulant activity. This interaction occurs with clinical grade heparin as well as with high affinity (for antithrombin III) heparin and with a high affinity heparin fragment with Mr. 4,300.Low affinity heparin competes with high affinity heparin for the binding to histidine-rich glycoprotein which results in an apparent increase of the anticoagulant activity of high affinity heparin.The interaction between heparin and histidine-rich glycoprotein is counteracted by Ca2+-binding anticoagulants, indicating that it is dependent on the presence of divalent metal ions. Ethylenediaminetetraacetate is a much more potent inhibitor of the interaction between heparin and histidine-rich glycoprotein than citrate.
Keywords: Heparin; Histidine-rich glycoprotein; Anticoagulant activity